Parenting Styles and Their Impact on Anxiety and Depression Symptoms ‎Among Higher Secondary Students - Dey, Snehanshu; Dash, lagnajit; Das, Jamuna; Anurag, Kirti (International Journal of Basic and Applied Sciences, 2025)
Background: Parenting styles play a critical role in shaping adolescent mental health. ‎Authoritative parenting is generally associated with positive psychological outcomes, while ‎authoritarian, permissive, and neglectful styles are often linked to increased emotional ‎distress. Amid growing academic and social pressures, understanding how parenting ‎approaches impact higher secondary students is essential for effective mental health support.‎Objectives: This study examined the relationship between parenting styles and levels of ‎anxiety and depression among higher secondary school students.‎Methods: A total of 72 Odia-medium students (48 boys, 24 girls) from Bhubaneswar, ‎Cuttack, and Puri in Odisha participated. All were from middle socio-economic backgrounds. ‎Parenting styles were assessed using the Parenting Style Questionnaire, while anxiety and ‎depression were measured using the Hamilton Anxiety Rating Scale and Hamilton Depression ‎Rating Scale. Data were analyzed using ANOVA, post-hoc comparisons, and chi-square tests.‎Results: Significant differences in anxiety [F(2, 71) = 9.41, p < .001] and depression [F(2, 71) ‎‎= 9.08, p < .001] were found across parenting styles. Permissive parenting was associated ‎with the highest levels of anxiety and depression, while authoritative parenting showed the ‎lowest. Chi-square analyses confirmed strong associations between parenting style and ‎severity of both conditions.‎Conclusion: Authoritative parenting may protect adolescents from anxiety and depression, ‎highlighting the importance of fostering supportive parenting practices‎.Key Highlights:‎• A significant association was found between parenting style and adolescent mental ‎‎• Authoritative parenting is linked to lower anxiety and depression levels.‎• Permissive parenting correlated with the highest mental health risks.‎• Strong statistical relationships confirmed through ANOVA and chi-square analysis.‎• Implications for parental guidance and adolescent support programs.‎
Keywords: Parenting Style; Anxiety; Depression; Adolescents; Authoritative Parenting; Permissive Parenting